Dianetics the modern science of mental health - Hubbard, L. Ron (La Fayette Ron), 1911-1986.; Sherr, Lloyd; Golden Era Productions (Los Angeles, Calif. : Golden Era Productions ; Commerce, CA : [Distributed by] Bridge Publications, 2009)
From the Introduction: Containing discoveries heralded as greater than the wheel or fire, Dianetics has remained a bestseller for more than 50 years. And with over 20 million copies in print, generating a movement that spans virtually every country on Earth, it's indisputably the most widely read and influential book ever written about the human mind. Here is the anatomy and full description of the Reactive Mind, the previously unknown source of nightmares, unreasonable fears, upsets and insecurities which enslave Man. This book shows you how to get rid of it, and so achieve something Man has previously only dreamed of: the State of Clear. Among the discoveries herein: The goal of man; The dynamic principle of existence-the one word that motivates all living things; The four dynamics-the drives upon which all of life is compartmented; The descriptic graph of survival-revealing one's true potential and how to achieve it; The discovery of and complete anatomy of the reactive mind; The painful experiences-engrams-contained in the reactive mind which command one to act irrationally against their own wishes and goals; The impact of prenatal engrams-what took place before you were born and how it's influenced you ever since; The complete Dianetics procedure to discover and eradicate these harmful experiences so they never affect you again, revealing the one person you've always wanted to know-you. This book is also accompanied by sixteen sound discs.
Disc 1: Dedication -- Synopsis -- How to read this book -- Book 1: Goal of man -- Chapter 1: Scope of Dianetics -- Chapter 2: Clear -- Disc 2: Chapter 3: Goal of man -- Chapter 4: Four Dynamics -- Chapter 5: Summary -- Disc 3: Book 2: Single source of all inorganic mental and organic psychosomatic ills -- Chapter 1: Analytical mind and the standard memory banks -- Chapter 2: Reactive mind -- Disc 4: Chapter 3: Cell and the organism -- Chapter 4: Demons -- Disc 5: Chapter 5: Psychosomatic illness -- Disc 6: Chapter 6: Emotion and the dynamics -- Chapter 7: Prenatal experience and birth -- Disc 7: Chapter 8: Contagion of aberration -- Chapter 9: Keying-in the engram -- Chapter 10: Preventive Dianetics -- Disc 8: Book 3: Therapy -- Chapter 1: Mind's protection -- Chapter 2: Release or clear -- Chapter 3: Auditor's role -- Chapter 4: Diagnosis -- Disc 9: Chapter 5: Returning, the file clerk and the time track -- Chapter 6: Laws of returning -- Disc 10: Chapter 6 (cont): Laws of returning -- Chapter 7: Emotion and the life force -- Disc 11: Chapter 7: Emotion and the life force -- Chapter 8: Some types of engrams -- Disc 12: Chapter 9 part 1: Mechanisms and aspects of therapy -- Disc 13: Chapter 9 part 1 (cont): Mechanisms and aspects of therapy -- Chapter 9 part 2: Mechanisms and aspects of therapy -- Disc 14: Chapter 9 part 2 (cont): Mechanisms and aspects of therapy -- Disc 15: Chapter 9 part 2 (cont): Mechanisms and aspects of therapy -- Disc 16: Chapter 9 part 2 (cont): Mechanisms and aspects of therapy -- Chapter 10: Dianetics-past and future.
Read by Lloyd Sherr.
"A Dianetics publication"--Container.
Case insert contains copyright date of 2009; book and discs have copyright date of 2007.
Compact discs.
Keywords: Dianetics; Mental health; Dianetics; Mental health; Audiobooks; Audiobooks